A photovoltaic roof waterproofing integrated system
By forming an integrated waterproof system on the photovoltaic roof, the combination of modified graphene oxide and hyperbranched SEBS elastomer is used to solve the problem of poor waterproofing performance of photovoltaic roofs and the residual dust and rain and snow affecting power generation efficiency, achieving more efficient waterproofing and pollution resistance.
Patent Information
- Application Number
- CN202310503721.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-06
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-05-06
AI Technical Summary
The heat generated by the photovoltaic roof during the energy conversion accelerates the thermal aging and ultraviolet aging of the waterproof layer, resulting in a degradation of waterproof performance. At the same time, dust and rain and snow residues affect the photovoltaic power generation efficiency.
The waterproof coating is applied to the top of the flexible thin-film photovoltaic cell, and the waterproof coil is bonded with an adhesive to form a photovoltaic roof waterproof integrated system. The waterproof coating of the system contains modified graphene oxide, enhancing the waterproof and electrical conductivity of the coating, while the waterproof coil improves its strength and heat resistance through the cross-linked structure of the hyperbranched SEBS elastomer.
It effectively improves the waterproof performance of photovoltaic roofs, avoids the reduction in photovoltaic power generation efficiency caused by dust and rain and snow residues, and at the same time enhances the anti-static and stain resistance of the coating.
Smart Images

Figure CN116591403B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of waterproofing, and in particular to an integrated photovoltaic roof waterproofing system. Background Art
[0002] In today's society where science and technology are developing rapidly, using clean energy such as electricity to replace traditional fossil energy and reduce environmental pollution has become the mainstream of development. Photovoltaic power generation is a technology that uses the photovoltaic effect of the semiconductor interface to directly convert light energy into electrical energy. It is an important part of vigorously developing electrical energy. The roof is the preferred location for photovoltaic power generation in buildings. The current photovoltaic construction on the roof often uses the form of installing crystalline silicon photovoltaic panels. Since crystalline silicon photovoltaic panels mostly use fixings to fix photovoltaic panels on the roof structure, this construction method will damage the original waterproof layer. Poor treatment of the punching place can easily cause leakage. Thin-film photovoltaic cells such as amorphous silicon are simple to construct and can be directly paved on the surface of the roof waterproof layer through adhesives. They have strong environmental adaptability and are gradually used in photovoltaic power generation on the roofs of factories and other buildings.
[0003] Since photovoltaic power generation is accompanied by a large amount of energy conversion, a large amount of heat will be generated during the energy conversion process. Especially in the hot summer weather, long-term exposure to the sun can easily accelerate the thermal aging and ultraviolet aging of the waterproof layer, resulting in damage to the waterproof layer and loss of the original waterproof effect. Therefore, the waterproof material of the photovoltaic roof needs to have not only good waterproof performance, but also good thermal stability and anti-ultraviolet performance. In addition, photovoltaic roofs often absorb dust in the air through electrostatic action, causing dust deposition, or rain and snow residues on the surface of photovoltaic modules after rain and snow. These residues will cause the photovoltaic modules to receive less solar energy, thereby affecting the efficiency of photovoltaic power generation. Based on this, the present invention forms a photovoltaic roof waterproof integrated system by coating a waterproof coating on the top of the flexible thin-film photovoltaic cell and bonding the waterproof roll material on the bottom with an adhesive to meet the waterproof requirements of the photovoltaic roof. Summary of the invention
[0004] The purpose of the present invention is to provide an integrated photovoltaic roof waterproofing system, which solves the problem of poor photovoltaic roof waterproofing performance and the problem of residual pollutants such as dust affecting photovoltaic power generation efficiency by coating a waterproof coating on the top of a flexible thin-film photovoltaic cell and bonding a waterproof roll material on the bottom with an adhesive.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A photovoltaic roof waterproofing integrated system, which comprises, from top to bottom, a waterproof coating, a flexible thin-film photovoltaic cell layer, an adhesive layer and a waterproof roll material layer;
[0007] The adhesive layer is formed by curing a polyurethane adhesive;
[0008] The waterproof coating is formed by spraying the waterproof coating on the upper surface of the flexible thin-film photovoltaic cell layer; the waterproof coating comprises the following raw materials in parts by weight: 60-70 parts of E-51 epoxy resin base material, 0.5-2 parts of modified graphene oxide, 1-3 parts of defoaming agent, 0.5-1 parts of leveling agent, and 20-30 parts of curing agent; the surface of the modified graphene oxide is grafted with fluorine-containing hydrophobic long chains and silicone;
[0009] The waterproof coiled material layer is formed by extruding the waterproof coiled material through an extrusion device, and then calendering, pulling and rolling; the waterproof coiled material comprises the following raw materials in parts by weight: 50-60 parts of polypropylene, 5-10 parts of hyperbranched elastomer, 0.5-1 part of plasticizer, 0.5-1 part of antioxidant and 2-5 parts of filler; the hyperbranched elastomer is prepared by cross-linking SEBS modified by maleic anhydride and benzophenone ultraviolet absorber with terminal amino polyamide as a cross-linking agent.
[0010] Furthermore, the defoaming agent is any one of BYK-A530 and BYK-A515; the leveling agent is any one of BYK-310 and BYK-315N; the curing agent is any one of p-phenylenediamine, ethylenediamine and diethylenetriamine; the plasticizer is any one of dimethyl phthalate and dioctyl phthalate; the antioxidant is any one of antioxidant 1010, antioxidant 1076 and antioxidant 168; the filler is any one of fumed silica and titanium dioxide.
[0011] Furthermore, the preparation method of the modified graphene oxide comprises the following steps:
[0012] Step A: dispersing graphene oxide in toluene, adding vinyl hydrogenated silicone oil, mixing, dropping a catalyst and stirring, passing nitrogen to deoxygenate, stirring at a temperature of 80-90° C. for 12-18 hours, discharging, centrifuging and separating solid materials, washing, and vacuum drying to obtain a graphene oxide intermediate;
[0013] Step B: Disperse the graphene oxide intermediate in ethyl acetate uniformly, continue to add perfluoroalkylthiol and benzoin dimethyl ether, stir evenly, pass nitrogen protection, place under ultraviolet light for 30-60 minutes, discharge, wash, and vacuum dry to obtain modified graphene oxide.
[0014] Furthermore, in step A, the hydrogen content of the vinyl hydrogenated silicone oil is 0.1%-1%.
[0015] Furthermore, in step A, the catalyst is trifluoroacetic acid.
[0016] Furthermore, in step B, the perfluoroalkylthiol is any one of 1H,1H,2H,2H-perfluorooctanethiol, 1H,1H,2H,2H-perfluorodecanethiol or 1H,1H,2H,2H-perfluorododecanethiol.
[0017] Through the above technical scheme, the surface of graphene oxide contains abundant oxygen-containing functional groups such as hydroxyl groups, which can react with Si-H bonds in the structure of vinyl hydrogen silicone oil under the action of the catalyst trifluoroacetic acid, and introduce the vinyl hydrogen silicone oil into the surface of graphene oxide to obtain an organosilicon-modified graphene oxide intermediate containing unsaturated olefinic functional groups. Since the perfluoroalkylthiol structure contains thiol groups, it can undergo a click reaction with the unsaturated olefinic groups on the surface of the graphene oxide intermediate under ultraviolet light conditions, thereby modifying the surface of graphene oxide with a large number of fluorinated hydrophobic long chains and organosilicon to obtain modified graphene oxide.
[0018] Furthermore, the preparation method of the hyperbranched elastomer comprises the following steps:
[0019] Step 1: Pour maleic anhydride, 4-allyloxy-2-hydroxybenzophenone and initiator into acetone and stir to dissolve, sprinkle the solution evenly on the surface of SEBS powder, transfer to a mixer, increase the temperature in the mixer to 70-80°C, stir for 5-10 minutes, transfer to a twin-screw extruder, set the screw speed to 40-50r / min, the extrusion temperature to 220-260°C, perform melt extrusion, discharge, and obtain modified SEBS;
[0020] Step 2: Evenly mix the amino-terminated hyperbranched polyamide, modified SEBS and xylene, add a catalyst and a promoter, mix well, pass nitrogen for protection, raise the system temperature to 90-100°C, stir for 6-12 hours, discharge the material, pour it into ethanol for precipitation, wash the obtained solid material thoroughly with ethanol, and vacuum dry it to obtain a hyperbranched elastomer.
[0021] Furthermore, in step 1, the initiator is any one of benzoyl peroxide or diisopropylbenzene peroxide.
[0022] Furthermore, in step 2, the number of amino groups in the amino-terminated hyperbranched polyamide is 7-9 mol.
[0023] Furthermore, in step 2, the mass ratio of the amino-terminated hyperbranched polyamide to the modified SEBS is 1:5-12.
[0024] Furthermore, in step 2, the catalyst promoter is p-toluenesulfonic acid.
[0025] Through the above technical scheme, under the action of an initiator, SEBS can generate free radicals in a high-temperature molten state, and undergo free radical polymerization reaction with maleic anhydride and unsaturated olefin groups in the structure of 4-allyloxy-2-hydroxybenzophenone, thereby obtaining maleic anhydride-modified SEBS containing a benzophenone ultraviolet absorber in the structure. Under the action of p-toluenesulfonic acid, the maleic anhydride groups in the structure can undergo condensation reaction with the amino groups in the amino-terminated hyperbranched polyamide structure, thereby forming a three-dimensional cross-linked hyperbranched SEBS elastomer with the amino-terminated hyperbranched polyamide as the core.
[0026] Furthermore, the preparation method of the waterproof integrated system comprises the following steps:
[0027] The first step: stir and mix the E-51 epoxy resin base material, defoamer and leveling agent in parts by weight, and let stand for 1-2 hours to obtain a premix ①; stir and mix the modified graphene oxide and the curing agent to obtain a premix ②; fully mix the premix ① and the premix ② to obtain a waterproof coating;
[0028] Step 2: Pour parts by weight of polypropylene, hyperbranched elastomer, plasticizer, antioxidant and filler into a mixer and mix them evenly, transfer the mixed materials to an extruder for melt extrusion, and then perform calendering, pulling and winding operations to obtain a waterproof roll;
[0029] Step 3: Spray the waterproof coating evenly on the top of the flexible thin-film photovoltaic cell. After the coating is cured, apply the adhesive to the bottom of the flexible thin-film photovoltaic cell layer and bond it to the waterproof membrane. After rolling and vacuuming, obtain a waterproof integrated system.
[0030] Beneficial effects of the present invention:
[0031] (1) The present invention prepares modified graphene oxide and fills it into the coating matrix as an additive. After the surface of the graphene oxide is modified, the van der Waals force between the flakes can be overcome by mechanical stirring, which is conducive to the uniform dispersion of the graphene oxide in the coating matrix. The uniformly dispersed graphene oxide flakes can not only form a physical barrier, extend the water penetration path, and improve the waterproof performance of the coating, but also form a conductive path to improve the conductivity of the coating, so that it has good antistatic properties, thereby effectively preventing fine particles such as dust from being adsorbed on the surface of the photovoltaic cell assembly through electrostatic action, causing the problem of reduced photovoltaic power generation efficiency. At the same time, the organic silicon and fluorine-containing hydrophobic long chains grafted on the surface of the graphene oxide have low surface energy, which can not only cooperate with the graphene oxide to combine physical barrier and chemical hydrophobicity to further enhance the waterproof performance of the coating, but also enhance the stain resistance of the coating, thereby avoiding the problem of reduced photovoltaic power generation efficiency due to rain and snow residue after rain and snow.
[0032] (2) The present invention prepares a hyperbranched SEBS elastomer, co-extrudes it with a polypropylene matrix and various additives, and then forms a waterproof coiled material through calendering, traction and winding operations. Since SEBS has good interfacial compatibility with the polypropylene matrix, the hyperbranched elastomer can be stably dispersed in the waterproof coiled material system, and a three-dimensional interpenetrating cross-linked network structure is formed in the waterproof coiled material system, which effectively enhances the binding force between the molecular chains of the polypropylene matrix and improves the cross-linking density of the polypropylene matrix, thereby enhancing the strength and waterproof performance of the waterproof coiled material. At the same time, a higher cross-linking density will limit the movement of the polypropylene molecular chain, which is beneficial to the improvement of the heat resistance of the waterproof coiled material. In addition, since the benzophenone ultraviolet absorber is chemically bonded to the hyperbranched elastomer structure, this chemical bond connection can stably disperse the ultraviolet absorber in the waterproof coiled material matrix without migration, so that the waterproof coiled material has anti-ultraviolet durability.
[0033] (3) The present invention forms an integrated photovoltaic roof waterproofing system by spraying waterproof coating on the top of the flexible thin-film photovoltaic cell and bonding waterproof membrane on the bottom. This system can not only avoid the problem of reduced photovoltaic power generation efficiency due to the deposition of dust, rain and snow, but also meet the waterproofing requirements of the photovoltaic roof through the dual waterproofing effects of waterproof coating and waterproof membrane.
[0034] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0036] Figure 1 This is a schematic diagram of the structure of a photovoltaic roof waterproofing integrated system of the present invention;
[0037] Figure 2 It is the infrared spectra of graphene oxide and modified graphene oxide in Example 1 of the present invention. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Example 1
[0040] 1. Preparation of modified graphene oxide
[0041] Step A: 0.5 g of graphene oxide is dispersed in toluene, 1.8 g of vinyl hydrogenated silicone oil is added, the mixture is mixed, 0.01 g of trifluoroacetic acid is added dropwise and stirred, nitrogen is passed through to deoxygenate, the mixture is stirred at 90° C. for 16 h, the mixture is discharged, the solid material is separated by centrifugation, washed, and vacuum dried to obtain a graphene oxide intermediate, wherein the hydrogen content of the vinyl hydrogenated silicone oil is 0.5%;
[0042] Step B: Disperse 0.2 g of graphene oxide intermediate in ethyl acetate, add 2.5 g of 1H,1H,2H,2H-perfluorodecanethiol and 0.01 g of benzoin dimethyl ether, stir well, pass nitrogen protection, irradiate under ultraviolet light for 40 min, discharge, wash, and vacuum dry to obtain modified graphene oxide.
[0043] Infrared analysis of graphene oxide and modified graphene oxide showed the following results: Figure 2 As shown by Figure 2 It can be observed that compared with graphene oxide, the modified graphene oxide has a -1 The hydroxyl absorption peak area at 1100-1250cm is reduced, which is speculated to be due to the reaction between the hydroxyl groups in the graphene oxide structure and the Si-H bonds in the vinyl hydrogenated silicone oil structure, which consumes some of the hydroxyl groups. -1 The stretching vibration peak of the CF bond appears at 908cm -1 1081cm -1 The absorption peak of Si-O bond appears at
[0044] 2. Preparation of waterproof coating
[0045] 60 parts of E-51 epoxy resin base material, 1 part of BYK-A530 defoamer and 0.5 parts of BYK-310 leveling agent were stirred and mixed, and allowed to stand for 1 hour to obtain premix ①; 0.5 parts of modified graphene oxide and 20 parts of p-phenylenediamine curing agent were stirred and mixed to obtain premix ②; premix ① and premix ② were fully mixed to obtain a waterproof coating.
[0046] Example 2
[0047] Preparation of waterproof coating
[0048] 65 parts of E-51 epoxy resin base material, 2 parts of BYK-A515 defoamer and 0.8 parts of BYK-315N leveling agent were stirred and mixed, and allowed to stand for 2 hours to obtain premix ①; 1 part of modified graphene oxide prepared in Example 1 of the present invention and 25 parts of ethylenediamine curing agent were stirred and mixed to obtain premix ②; premix ① and premix ② were fully mixed to obtain a waterproof coating.
[0049] Example 3
[0050] Preparation of waterproof coating
[0051] 70 parts of E-51 epoxy resin base material, 3 parts of BYK-A515 defoamer and 1 part of BYK-315N leveling agent were stirred and mixed, and allowed to stand for 2 hours to obtain a premix ①; 2 parts of modified graphene oxide prepared in Example 1 of the present invention and 30 parts of diethylenetriamine curing agent were stirred and mixed to obtain a premix ②; premix ① and premix ② were fully mixed to obtain a waterproof coating.
[0052] Comparative Example 1
[0053] Preparation of waterproof coating
[0054] 65 parts of E-51 epoxy resin base material, 2 parts of BYK-A515 defoamer and 0.8 parts of BYK-315N leveling agent were stirred and mixed, and allowed to stand for 2 hours to obtain premix ①; 25 parts of diethylenetriamine curing agent were poured into premix ①, and mixed thoroughly to obtain a waterproof coating.
[0055] Example 4
[0056] 1. Preparation of Hyperbranched Elastomers
[0057] Step 1: Pour 6g of maleic anhydride, 2.5g of 4-allyloxy-2-hydroxybenzophenone and 0.1g of diisopropylbenzene peroxide into acetone and stir to dissolve, sprinkle the solution evenly on the surface of 10g of SEBS powder, transfer to a mixer, increase the temperature in the mixer to 80°C, stir for 5min, transfer to a twin-screw extruder, set the screw speed to 40r / min, the extrusion temperature to 240°C, perform melt extrusion, discharge, and obtain modified SEBS;
[0058] Accurately weigh 1g of modified SEBS sample and pour it into 50mL of xylene to mix. Raise the temperature to 100℃ and stir until a uniform solution is formed. After natural cooling, add an excess of 0.1M KOH-methanol standard solution to the solution. Raise the temperature to 140℃ again, reflux for 6h and then cool naturally. Add 0.1mL of phenolphthalein indicator and use 0.1M HCl-isopropanol standard solution to back-titrate the excess KOH-methanol standard solution until the solution changes color. Record the excess alkali consumed V1 (mL) and the neutralized acid V2 (mL). Use the following formula
[0059]
[0060] Calculate the mass fraction T (%) of maleic anhydride in the sample, where C1 is the concentration of KOH-methanol standard solution (mol / L); C2 is the concentration of HCl-isopropanol standard solution (mol / L); m is the sample weight (g). After calculation, the mass fraction of maleic anhydride in the sample is 1.94%.
[0061] Step 2: 1g of amino-terminated hyperbranched polyamide, 12g of modified SEBS and xylene are mixed evenly, 0.2g of p-toluenesulfonic acid is added and mixed, nitrogen protection is passed, the system temperature is raised to 100°C, stirred for 9h, the material is discharged, poured into ethanol for precipitation, ethanol is used to fully wash the obtained solid material, and vacuum dried to obtain a hyperbranched elastomer, wherein the amino number of the amino-terminated hyperbranched polyamide is 8mol. The mass fraction of maleic anhydride in 1g of the hyperbranched elastomer sample is tested using the same titration method as step 1. After testing, the mass fraction of maleic anhydride in the sample is 0.21%, because the terminal amino group in the amino-terminated hyperbranched polyamide structure condenses with the maleic anhydride group in the modified SEBS structure, consuming a large amount of maleic anhydride groups.
[0062] 2. Preparation of waterproof membrane
[0063] Pour 50 parts of polypropylene, 5 parts of hyperbranched elastomer, 0.5 parts of dimethyl phthalate, 0.5 parts of antioxidant 1010 and 2 parts of fumed silica into a mixer and mix well. Transfer the mixed materials to an extruder for melt extrusion, and then perform calendering, pulling and winding operations to obtain a waterproof membrane.
[0064] Example 5
[0065] Preparation of waterproof membrane
[0066] 55 parts of polypropylene, 8 parts of the hyperbranched elastomer prepared in Example 4 of the present invention, 0.6 parts of dioctyl phthalate, 0.8 parts of antioxidant 1076, and 3 parts of titanium dioxide are poured into a mixer and mixed evenly. The mixed materials are transferred to an extruder for melt extrusion, and then calendered, pulled and rolled to obtain a waterproof membrane.
[0067] Example 6
[0068] Preparation of waterproof membrane
[0069] 60 parts of polypropylene, 10 parts of the hyperbranched elastomer prepared in Example 4 of the present invention, 1 part of dimethyl phthalate, 1 part of antioxidant 168, and 5 parts of titanium dioxide are poured into a mixer and mixed evenly. The mixed materials are transferred to an extruder for melt extrusion, and then calendered, pulled and rolled to obtain a waterproof membrane.
[0070] Comparative Example 2
[0071] Preparation of waterproof membrane
[0072] 55 parts of polypropylene, 0.6 parts of dioctyl phthalate, 0.8 parts of antioxidant 1076 and 3 parts of titanium dioxide are poured into a mixer and mixed evenly. The mixed materials are transferred to an extruder for melt extrusion, and then calendered, pulled and rolled to obtain a waterproof membrane.
[0073] Performance Testing
[0074] a. The waterproof coatings prepared in Examples 1 to 3 of the present invention and Comparative Example 1 were uniformly coated on the surface of the cleaned steel plate, and the coating thickness was controlled to be 10 um. After the coating was completely cured, the coating was taken out, and the surface resistivity of the coating was tested according to the standard SJ / T 11294-2003, and the antistatic performance of the coating was evaluated; the waterproof performance of the coating was tested according to the national standard GB / T 16777-2008, with the metal mesh aperture set to (0.5±0.1) mm, the test pressure to 0.5 MPa, and the test time to 1 h; the water contact angle of the coating was tested using an SDC-100S contact angle tester to evaluate the hydrophobic performance of the coating; the test results are shown in the following table:
[0075] Example 1 Example 2 Example 3 Comparative Example 1 <![CDATA[Surface resistivity (Ω / cm 2 )]]> 0.3 0.2 0.2 2.6 Water seepage impermeable impermeable impermeable permeable Water contact angle (°) 151.4 152.1 152.0 93.9
[0076] As can be seen from the above table, the waterproof coatings prepared in Examples 1 to 3 of the present invention have low surface resistivity, strong antistatic properties, and a water contact angle greater than 150°, so they have super hydrophobic surfaces and good waterproof properties, which can prevent fine particles such as dust from being adsorbed on the surface of photovoltaic cell modules through electrostatic action and avoid the problem of reduced photovoltaic power generation efficiency caused by residual rain and snow after rain and snow. The waterproof coating prepared in Comparative Example 1 does not add modified graphene oxide, so the surface resistivity is high, the antistatic properties are poor, and water permeability occurs in the waterproof performance test, the waterproof performance is general, and the water contact angle is less than 100°. Although it has certain hydrophobic properties, the hydrophobic effect is not strong, and it is difficult to avoid the problem of poor photovoltaic power generation effect caused by dust deposition and residual rain and snow.
[0077] b. With reference to the national standard GB / T 328-2007, the waterproof membranes prepared in Examples 4 to 6 of the present invention and Comparative Example 2 were tested for tensile strength, tear strength and waterproof performance, wherein the waterproof performance is characterized by the pressure value of 30-min water permeability. Generally speaking, the larger the pressure value, the better the waterproof performance, and vice versa. The waterproof membranes prepared in Examples 4 to 6 of the present invention and Comparative Example 2 were cut into samples of the same specifications, placed in a UV aging box, and the radiation intensity was set to 0.35 W / m 2 , record the time when the sample turns yellow under ultraviolet light, and evaluate its anti-ultraviolet performance; take the waterproof membranes prepared in Examples 4 to 6 of the present invention and Comparative Example 2 of the same mass, place them in a TGA-601 thermogravimetric analyzer, and under nitrogen protection, increase the temperature from room temperature to 800°C, record its initial decomposition temperature, and evaluate the heat resistance of the waterproof membranes. The test results are shown in the following table:
[0078] Example 4 Example 5 Example 6 Comparative Example 2 Tensile strength(MPa) 20 23 21 16 Tear strength(N / mm) 83 86 85 61 Waterproof performance (MPa) 0.72 0.78 0.77 0.24 Yellowing time >2 years >2 years >2 years <3 months Initial decomposition temperature (℃) 386.9 389.5 388.2 368.1
[0079] It can be seen from the above table that the waterproof membranes prepared in Examples 4 to 6 of the present invention have high strength, good UV resistance, good heat resistance and excellent waterproof performance, while the waterproof membrane prepared in Comparative Example 1 does not contain any hyperbranched elastomer, and cannot utilize the hyperbranched elastomer to cross-link with the polypropylene base material to form a three-dimensional interpenetrating cross-linked network structure in the waterproof membrane system. Therefore, the strength is relatively low, and the heat resistance, UV resistance and waterproof performance are all poor.
[0080] The waterproof coating prepared by the examples 1 to 3 of the present invention and the waterproof coiled material prepared by the examples 4 to 6 of the present invention are respectively used to prepare the waterproof integrated system. The preparation method is as follows: the waterproof coating is uniformly sprayed on the top of the flexible thin-film photovoltaic cell. After the coating is cured, the polyurethane adhesive is coated on the bottom of the flexible thin-film photovoltaic cell layer and adhered to the waterproof coiled material. After rolling and vacuum treatment, the waterproof integrated system is obtained. The structure of the waterproof integrated system is as follows Figure 1 shown.
[0081] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A photovoltaic roof waterproofing integrated system, characterized in that: From top to bottom, it includes a waterproof coating, a flexible thin-film photovoltaic cell layer, an adhesive layer and a waterproof roll material layer; The adhesive layer is formed by curing a polyurethane adhesive; The waterproof coating is formed by spraying the waterproof coating on the upper surface of the flexible thin-film photovoltaic cell layer; the waterproof coating comprises the following raw materials in parts by weight: 60-70 parts of E-51 epoxy resin base material, 0.5-2 parts of modified graphene oxide, 1-3 parts of defoaming agent, 0.5-1 parts of leveling agent, and 20-30 parts of curing agent; the surface of the modified graphene oxide is grafted with fluorine-containing hydrophobic long chains and silicone; The waterproof coiled material layer is formed by extruding the waterproof coiled material through an extrusion device, and then calendering, pulling and rolling; the waterproof coiled material comprises the following raw materials in parts by weight: 50-60 parts of polypropylene, 5-10 parts of hyperbranched elastomer, 0.5-1 part of plasticizer, 0.5-1 part of antioxidant and 2-5 parts of filler; the hyperbranched elastomer is prepared by cross-linking SEBS modified by maleic anhydride and benzophenone ultraviolet absorber with terminal amino polyamide as a cross-linking agent.
2. A photovoltaic roof waterproofing integrated system according to claim 1, characterized in that: The defoaming agent is any one of BYK-A530 and BYK-A515; the leveling agent is any one of BYK-310 and BYK-315N; the curing agent is any one of p-phenylenediamine, ethylenediamine and diethylenetriamine; the plasticizer is any one of dimethyl phthalate and dioctyl phthalate; the antioxidant is any one of antioxidant 1010, antioxidant 1076 and antioxidant 168; the filler is any one of fumed silica and titanium dioxide.
3. The photovoltaic roof waterproofing integrated system according to claim 1, characterized in that: The preparation method of the modified graphene oxide comprises the following steps: Step A: dispersing graphene oxide in toluene, adding vinyl hydrogenated silicone oil, mixing, dropping a catalyst and stirring, passing nitrogen to deoxygenate, stirring at a temperature of 80-90° C. for 12-18 hours, discharging, centrifuging and separating solid materials, washing, and vacuum drying to obtain a graphene oxide intermediate; Step B: Disperse the graphene oxide intermediate in ethyl acetate uniformly, continue to add perfluoroalkylthiol and benzoin dimethyl ether, stir evenly, pass nitrogen protection, place under ultraviolet light for 30-60 minutes, discharge, wash, and vacuum dry to obtain modified graphene oxide.
4. A photovoltaic roof waterproofing integrated system according to claim 3, characterized in that: In step A, the hydrogen content of the vinyl hydrogen-containing silicone oil is 0.1%-1%.
5. The photovoltaic roof waterproofing integrated system according to claim 3, characterized in that: In step A, the catalyst is trifluoroacetic acid.
6. The photovoltaic roof waterproofing integrated system according to claim 3, characterized in that: In step B, the perfluoroalkylthiol is any one of 1H,1H,2H,2H-perfluorooctanethiol, 1H,1H,2H,2H-perfluorodecanethiol or 1H,1H,2H,2H-perfluorododecanethiol.
7. The photovoltaic roof waterproofing integrated system according to claim 1, characterized in that: The preparation method of the hyperbranched elastomer comprises the following steps: Step 1: Pour maleic anhydride, 4-allyloxy-2-hydroxybenzophenone and initiator into acetone and stir to dissolve, sprinkle the solution evenly on the surface of SEBS powder, transfer to a mixer, increase the temperature in the mixer to 70-80°C, stir for 5-10 minutes, transfer to a twin-screw extruder, set the screw speed to 40-50r / min, the extrusion temperature to 220-260°C, perform melt extrusion, discharge, and obtain modified SEBS; Step 2: Evenly mix the amino-terminated hyperbranched polyamide, modified SEBS and xylene, add a catalyst and a promoter, mix well, pass nitrogen for protection, raise the system temperature to 90-100°C, stir for 6-12 hours, discharge the material, pour it into ethanol for precipitation, wash the obtained solid material thoroughly with ethanol, and vacuum dry it to obtain a hyperbranched elastomer.
8. The photovoltaic roof waterproofing integrated system according to claim 7, characterized in that: In step 1, the initiator is any one of benzoyl peroxide or diisopropylbenzene peroxide.
9. The photovoltaic roof waterproofing integrated system according to claim 7, characterized in that: In step 2, the amino group number of the amino-terminated hyperbranched polyamide is 7-9 mol.
10. The photovoltaic roof waterproofing integrated system according to claim 7, characterized in that: In step 2, the mass ratio of the amino-terminated hyperbranched polyamide to the modified SEBS is 1:5-12.
11. The photovoltaic roof waterproofing integrated system according to claim 7, characterized in that: In step 2, the catalyst promoter is p-toluenesulfonic acid.
12. The photovoltaic roof waterproofing integrated system according to claim 1, characterized in that: Preparation method of the waterproof integrated system The following steps are involved: The first step: stir and mix the E-51 epoxy resin base material, defoamer and leveling agent in parts by weight, and let stand for 1-2 hours to obtain a premix ①; stir and mix the modified graphene oxide and the curing agent to obtain a premix ②; fully mix the premix ① and the premix ② to obtain a waterproof coating; Step 2: Pour parts by weight of polypropylene, hyperbranched elastomer, plasticizer, antioxidant and filler into a mixer and mix them evenly, transfer the mixed materials to an extruder for melt extrusion, and then perform calendering, pulling and winding operations to obtain a waterproof roll; Step 3: Spray the waterproof coating evenly on the top of the flexible thin-film photovoltaic cell layer. After the coating is cured, apply the adhesive to the bottom of the flexible thin-film photovoltaic cell layer and bond it to the waterproof membrane. After rolling and vacuuming, obtain a waterproof integrated system.
Citation Information
Patent Citations
High-strength antibacterial thermoplastic elastomer and preparation method thereof
CN106883593A
Rubber diaphragm and preparation method thereof
CN108395663A